A hexagonal shape-persistent nanobelt of elongated rhombic symmetry with orthogonal π-planes by a one-pot reaction [data] - Lauer, Jochen; Kohl, Bernd; Rominger, Frank; Mastalerz, Michael (Universität, 2022)
Triptycenes with their predefined D3h-symmetry are excellent molecular building blocks to construct shape-persistent nanobelts having π-orbitals or...